Effects of Market-Sensing Capability on Marketing Performance: Roles of Pious Product Innovativeness and the Speed to Market Strategy - ., Mulyana; Sari, Afriana Indah (Jurnal Manajemen Teknologi, 2021)
Abstract. This paper examines the effects of pious product innovativeness (PPI) and the speed to market strategy (SMS) as mediating variables between market-sensing capability (MSC) and marketing performance (MP). The respondents were 237 leaders or owners of small and medium Muslim fashion enterprises in Central Java. The data analysis technique used in this study was structural equation modeling (SEM). The results of the study indicate that although MSC does not affect MP, it affects both the SMS and PPI. Moreover, the SMS and PPI affect MP. Furthermore, the SMS and innovative products mediate the relationship between MSC and market performance. Likewise, PPI mediates the relationship between the SMS and market performance.Keywords: Market-sensing capability, speed to market strategy, pious product innovativeness, marketing performance.Abstrak. Makalah ini meneliti efek dari pious product innovativeness (PPI) dan speed to market strategy (SMS) sebagai variabel mediasi antara market-sensing capability (MSC) dan marketing performance (MP). Respondennya adalah 237 pemimpin atau pemilik usaha fashion muslim kecil dan menengah di Jawa Tengah. Teknik analisis data yang digunakan dalam penelitian ini adalah structural equation modeling (SEM). Hasil penelitian menunjukkan bahwa meskipun MSC tidak mempengaruhi MP, namun mempengaruhi SMS dan PPI. Selain itu, SMS dan PPI mempengaruhi MP. Selain itu, SMS dan produk inovatif memediasi hubungan antara MSC dan kinerja pasar. Demikian juga, PPI memediasi hubungan antara SMS dan kinerja pasar.Kata kunci: Market-sensing capability, speed to market strategy, pious product innovativeness, marketing performance